PREHISTORICAL TSUNAMIS IN KRONOTSKII GULF, KAMCHATKA, RUSSIA: A PROGRESS REPORT - Pinegina T.K.; Bazanova L.I.; Melekestsev I.V.; Braitseva O.A.; Storcheus A.V.; Gusyakov V.K. (My University, 2000)
For the first time in Kamchatka, 47 paleotsunamis that had hit the shore of the Kronotskii Gulf during Holocene time were identified and dated using a tephrochronological method. The data for the time period from 3000 B.P. to the present were examined to estimate the recurrence of tsunamis having a well-pronounced peak of activity 1500-2000 B.P. during the all-Kamchatka period of increased seismicity and a simultaneous increase in volcanic activity.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен